Boron-mediated aluminium stress tolerance under aluminium toxicity at germination and early seedling stages of wheat (Progressive Agriculture, 2022)
Aluminium stress is one of the major problems of wheat production that significantly reduces the growth and development. Al toxicity can be recovered by exogenous application of different growth inducing nutrient elements. Thus, this study was conducted to evaluate the ameliaration effect of B under Al toxicity. Therefore, a petri dish and hydroponic culture experiment of wheat was conducted at Crop Physiology Laboratory, Department of Crop Botany, Bangladesh Agricultural University, Mymensingh during the period from January 2016 to February 2017 to investigate the effect of boron on amelioration of aluminium toxicity in germination and seedling stage. Both the experiments were designed in completely randomized design (CRD) with three replications. The experiments were comprised of four levels of boron and aluminium concentrations viz., 0 µM B + 0 µM Al (control), 0 µM Al + 40 µM B, 200 µM Al + 40 µM B and 0 µM B + 200 µM Al and five wheat varieties viz; BARI Gom-23, BARI Gom-24, BARI Gom-28, BARI Gom-27 and BARI Gom-30. Results indicated that germination percentage, radicle and plumule length, root and shoot length, leaf length, fresh and dry mass   plant-1 were greater in 0 µM Al + 40 µM B treated plants than 0 µM B + 200 µM Al induced conditions. It indicates that wheat seedlings are susceptible to aluminium and boron can ameliorate aluminium toxicity. However, among the studied varieties, the reduction of dry mass under aluminium stress was minimum in BARI Gom-28 followed by BARI Gom-23 indicating BARI Gom-28 was more tolerant to aluminium stress than the other varieties. On the contrary, the varieties, BARI Gom-27 and BARI Gom-24 were more susceptible to aluminium stress. So it indicates that aluminium stress severely affects the growth and developments especially in the sensitive varieties and tolerant varieties have the self-ability to grow and develop even under aluminium stress condition.Progressive Agriculture 32 (2): 127-139, 2021